Analysis of trace elements accumulation in some landscape plants as an indicator of pollution in an urban environment: Case of Ankara - Ahmi̇da Saleh, Elnaji Abdulaziz; Işinkaralar, Öznur (Kastamonu Üniversitesi, 2022)
As a result of the increase in structure and population densities in urban areas, many problems arise in cities that need to be solved. With the effect of keeping the planned approaches to air pollution in the city's background, urban air pollution has started to feel serious with the adverse effects it has created on living things. Heavy metals, which are one of the components of air pollution, seriously threaten living things because they cannot be eliminated from metabolism. For this reason, heavy metal pollution should be monitored in order to make the necessary interventions. The research aims to interpret the trace element level by using Cupressus sempervirens L. Thuja occidentalis L. Platanus orientalis L. Prunus cerasifera Ehrh. and Photinia serrulata Lindl. plants in the city center of Ankara as biomonitors. In this context, variance analysis was performed on lead and cadmium concentration levels with the SPSS package program. The mean values were subjected to the Duncan test for multiple comparison purposes. The difference in the accumulation levels of plant species and organs was revealed due to the research.
Keywords: Engineering; Urban Air Quality; Trace Elements; Accumulation; Biomonitoring; Ankara; Mühendislik; 13. Climate action; 11. Sustainability; 6. Clean water